43P Enhancing the therapeutic effect of dendritic cell therapy by oncolytic adenovirus 3 encoding CD40-ligand. (15th December 2019) - Zafar, S; Quixabeira, D C A; Hemminki, O; Cervera-Carrascon, V; Santos, J M; Kanerva, A; Hemminki, A
Abstract: Background: Dendritic Cell (DC) therapy is considered as a promising immunotherapeutic approach for treatment of advanced cancer. However, the tumor microenvironment is highly immunosuppressive that leads to DC dysfunction. Therefore, in clinical trials DC therapy has generally failed to fulfill its expectations. Oncolytic adenoviruses are well tolerated and have shown to preferentially target and kill cancer cells. Therefore, to improve the therapeutic efficacy of DC therapy, we armed oncolytic adenovirus with CD40 ligand (CD40L). CD40L is well known to regulate immune responses through its capacity to stimulate dendritic cells that lead to the activation of cytotoxic T-cells. Methods: In this study, we generated a novel virus Ad3-hTERT-CMV-hCD40L (Ad3-hCD40L), which is fully serotype 3 adenovirus. It features a human telomerase reverse transcriptase promoter for tumor specificity and expresses human CD40L (hCD40L) under a cytomegalovirus promoter for induction of antitumor immune responses. Animal experiments were implanted in immunocompetent and in humanized mice model. To further deeply dissect if Ad3-hCD40L can modulate tumor microenvironment, tumor histocultures derived from prostate patients were used. Results: In syngeneic studies in animal models, DC therapy with Ad3-hCD40L showed significant antitumor immune response. This enhanced therapeutic effect is associated with increased tumor specific T-cells and induction of T-helper type 1 immune response. Moreover, Ad3-hCD40L and human DCs showed 100 percent survival in conjunction with tumor control. Tumor histocultures treated with Ad3-hCD40L showed that virally expressed hCD40L in the tumor microenvironment leads to significant activation of dendritic cells and induction of Th1 immune response. Conclusion: To conclude, CD40L armed oncolytic adenovirus 3 improves DC therapy by favorable alteration of tumor microenvironment. These findings support clinical trials where DC therapy is enhanced with oncolytic adenovirus. Legal entity responsible for the study: Cancer Gene Therapy Group, University of Helsinki. Funding: University of Helsinki. Disclosure: V. Cervera-Carrascon: Full / Part-time employment: TILT Biotherapeutics Ltd. J.M. Santos: Full / Part-time employment: TILT Biotherapeutics Ltd. A. Hemminki: Shareholder / Stockholder / Stock options, Full / Part-time employment, Officer / Board of Directors: TILT Biotherapeutics Ltd. All other authors have declared no conflicts of interest.